Dental evaluation prior to radiotherapy treatment in patients with cancer in the head and neack region (Research, Society and Development, 2022)
Objective:  To evaluate the dental condition and describe the need to adapt the oral environment prior to radiotherapy treatment in patients with cancer in the head and neck region. Methodology: A cross-sectional study was carried out with 103 patients diagnosed with head and neck cancer with indication for treatment with radiotherapy, through an interview with the patient and clinical examination. Sociodemographic data of the patient, information on the oncological disease, indication and dental treatments performed were collected. Results: Only 19% of the sample had an indication for surgical treatment, 66% for chemotherapy and all had an indication for three-dimensional RT, with an average dose of 63.5 Gy. Regarding oral hygiene habits, 82% reported brushing their teeth at least once a day and 88% reported never having used dental floss. An average of 14 teeth present per patient was observed, 76% had extraction indicated in the treatment plan and the most frequent reason was root exposure/furcation lesion (46%). 62% of the patients completed all the indicated dental treatment and there was an average of 18 days between screening and discharge for initiation of radiotherapy. Conclusion: Most of the population performed the adequacy of the complete oral cavity and in a timely manner to start radiotherapy. Access to health services and the possibility of adhering to dental follow-up after radiotherapy should be taken into account when planning treatment.